Webinar Learning Strategies: Efforts to Increase Student’s Activeness and Learning Achievements in the New Normal Period in Public Policy Course - Evi Susilawati; Imamul Khaira (Nusantara Science and Technology Proceedings, 2021)
Because to improve student activities and learning outcomes in this pan-demic mass is the teacher's main task. To develop these competencies, one option is to use a seminar website or webinar as a learning strategy that can be applied to students. However, little is known about the process of improving student activity and learning outcomes through webinars. The purpose of this study was to increase student activity and learning outcomes during the pandemic in public policy courses through webinar learning strategies. This study uses classroom action research methods which were carried out at the Islamic University of North Sumatra with the participation of 10 students. The instruments used in this study were observation sheets, student assessments, and interview sheets. The results showed that there was an increase in student learning activities, especially in refuting activities or accepting other friends' ideas. The results of this classroom action research show that there is an increase in the activeness and learning achievements of students during the New Normal period in the public policy course using the webinar strategy.